(untitled) (Applied Biological Research, 2024)
Background and Purpose: Professional workers frequently experience occupational stress. This also applies to female employees. Such stress is negatively impacting health indicators, particularly sleep disturbance. The study aims to determine the degree of work stress, health issues, sleep patterns and nutritional anthropometric parameters like body fat percentage(BF%), waist circumference(WC), waist-hip ratio(WHR) status.Materials/Method: By using Occupational Stress Index(OSI) scale, Pittsburgh Sleep Quality Index(PSQI) and Physical Health Questionnaire(PHQ), responses were collected including socio-demographic, professional data from female customer service associates (n=103) by simple random sampling method in Kolkata. Bio-electric Impedance based Body Composition Analyzer, anthropometric measurements were also involved.Results: The study finds that significant number of subjects are having moderate work stress(mean OSI score 133.40±19.41), sleep disturbances(mean PSQI Global score 6.71±3.31), including physical health problems respecting headache, sleep disturbance.Subjects are having significantly high mean for body fat% (33.46±7.91) and (37.83±5.08) among (20-39)years and (40-59)years age group respectively, WC (84.43±10.43) and WHR (1.05±1.88) indicating abdominal obesity, poor nutritional condition.Conclusion: The study is vital to address the health concerns among working females with a particular focus on nutritional health conditions. A well-executed nutritional health plan, with a focus on nutrition and lifestyle education, can help to prevent this.